Occupational Chemical Exposures among Cosmetologists: Risk of Reproductive Disorders. (December 2013) - Pak, Victoria M.; Powers, Martha; Liu, Jianghong
More research is needed to understand possible occupational reproductive risks for cosmetologists, specifically hairdressers and nail technicians, two occupations that often share workspace and exposure to hair dyes and nail polish. Cosmetologists are predominantly females of reproductive age; thus, they may be at higher risk for the effects of exposure to reproductive toxins. The purpose of this article is to inform nurses and public health professionals about occupational exposures for cosmetologists and discuss interventions to reduce the risks of reproductive disorders among susceptible worker populations.